2015
DOI: 10.47552/ijam.v6i3.630
|View full text |Cite
|
Sign up to set email alerts
|

Antistress Activity of Tinospora Cordifolia with Application of Yoga

Abstract: Aim: Mental stress can lead to various biochemicals, physiological and psychological changes in human body. The present study was designed to evaluate the antistress activities of Tinospora cordifolia (wild) Miers associated with yogaMethods:  A randomized double blind placebo control 8 weeks study was conducted. The mental stress patients were diagnosed clinically by using different validated psychological rating scales. A total of 63 patients with mental stress were randomized into four groups. The antistre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…48 A randomized, double-blind placebo control study has shown that Tinospora cordifolia treatment in combination with yoga helps to reduce mental stress in patients. 49 A decrease in catalase, SOD, GSH, and an increase in MDA/LPO level, as well as neuronal damage in the cortex and hippocampus regions of the brain, were all signs indicating a considerable increase in oxidative stress in the brain following aluminium chloride therapy in the current study. According to earlier research, aluminium stimulates and activates LPO when there is iron present in the brain.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…48 A randomized, double-blind placebo control study has shown that Tinospora cordifolia treatment in combination with yoga helps to reduce mental stress in patients. 49 A decrease in catalase, SOD, GSH, and an increase in MDA/LPO level, as well as neuronal damage in the cortex and hippocampus regions of the brain, were all signs indicating a considerable increase in oxidative stress in the brain following aluminium chloride therapy in the current study. According to earlier research, aluminium stimulates and activates LPO when there is iron present in the brain.…”
Section: Discussionsupporting
confidence: 59%
“…48 A randomized, double-blind placebo control study has shown that Tinospora cordifolia treatment in combination with yoga helps to reduce mental stress in patients. 49…”
Section: Discussionmentioning
confidence: 99%